Bug boys : outside and beyond - Knetzger, Laura, 1990-; Lynde, Lyle (New York : RH Graphic, 2021)
Follows two bug friends, Stag-B and Rhino-B, as they explore their world and share adventures.
"Originally published in the United States in black and white and in different form by Czap Books, Providence, Rhode Island, in 2015."
Ages 7-10
Grades 2-3
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Graphic novels; Insects -- Fiction; Adventure and adventurers -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Action and adventure comics; Graphic novels